Analisis Pengaruh Penggunaan Fly Ash Batu Bara Dan Abu Batu Sebagai Filler Pada Campuran Laston Lapis Aus (AC-WC) - Rinaldi Basri, Doni; Ningrum, Puspa; Adi Poetra, Akram (Sekolah Tinggi Teknologi Pekanbaru, 2024)
Coal fly ash has been categorized as factory waste therefore We should reduce factory waste and utilize it wisely optimal. In this research, coal fly ash and ash were used stone as an alternative to filler in AC-WC mixtures. The purpose of this research is to determine the marshall characteristics of the AC-WC layer with using a combination of coal fly ash and rock ash fillers. Research methods used in this research was an experimental method of varying the levels of coal fly ash filler and rock ash combined, namely 0%- 100%, 50%-50%, 60%-40%, 70%-30%, 80%-20%, 90%-10%, and 100%-0%.The specifications used in this research are General Bina Marga Specifications 2018 Revision 2. The optimum asphalt content obtained was 5.9%. Based on the results of Marshall testing variations of coal fly ash and stone ash fillers The best in this research was the variation of 50% coal fly ash and 50% rock ash. This is shown based on the stability value the composition obtains The stability value is 1,976.10 kg and the MQ value is 640.89 kg/mm with The melting value is 3.08 mm so it can be concluded that the quality of the AC-WC is the best In this research there are filler variations of 50% coal fly ash and 50% rock ash.